Self-assembled aggregate material as well as preparation method and application thereof
Through the combination of polyethylene glycol, siligotrous acid and astaxanthin, the use of hydrogen bonds to drive molecular self-assembly, the problem of existing aggregate materials being susceptible to environmental factors is solved, the adhesion and injection performance are improved, and the adhesion and injection performance are given. It has antibacterial, antioxidant and anti-inflammatory properties, and has achieved efficient preparation and application of self-assembled aggregate materials.
Patent Information
- Application Number
- CN202411410551.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-10
- Publication Date
- 2025-01-03
AI Technical Summary
Existing aggregate materials are susceptible to factors such as pH, ionic strength, concentration and relative molecular mass, have poor adhesion, poor injection performance, and complex preparation processes, which limit their development and commercial application.
Polyethylene glycol, siligotungstic acid and astaxanthin are used as raw materials to drive molecular self-assembly through hydrogen bonding to form a translucent and dense condensed phase, improve adhesion strength and injection performance, and introduce antibacterial and antioxidant through astaxanthin. and anti-inflammatory properties.
It realizes the high adhesion strength, excellent injection performance, antibacterial, antioxidant and anti-inflammatory properties of the aggregate material, reduces production costs, and is suitable for large-scale production and application.
Smart Images

Figure CN119236171A_ABST
Abstract
Description
Technical Field
[0001] The present application belongs to the technical field of medical materials, and in particular relates to a self-assembled condensate material and a preparation method and application thereof. Background Art
[0002] Coacervate materials have independent physical and chemical properties such as high polymer density, low interfacial tension, water immiscibility, adhesion and self-healing ability. They can diffuse on the tissue surface by repelling interfacial water, making them excellent candidate materials for wound healing. Existing coacervate materials are usually formed by electrostatic interactions between polyelectrolytes of opposite charges, but are easily affected by various factors such as pH, ionic strength, mixing ratio, concentration and relative molecular mass, which greatly limits their development and commercial application. Therefore, it is necessary to develop coacervate materials with excellent comprehensive performance.
[0003] The existing condensate materials have the following problems: First, the existing condensate materials are driven by electrostatic action, which is easily affected by factors such as pH and concentration, and can only form condensation under specific pH and concentration. They will become ineffective outside this range; second, the adhesion is poor, which is not conducive to staying on the wound surface; third, the injection performance is poor, which is not conducive to wide application; fourth, the preparation process is complicated, which is not conducive to large-scale production. Summary of the invention
[0004] The present application discloses a self-assembled condensate material and a preparation method and application thereof, aiming to solve the technical problems of existing condensate materials such as multiple influencing factors, poor adhesion, poor injectability and complicated preparation.
[0005] In order to achieve the above purpose, the technical solution of this application is:
[0006] The first aspect of the present application provides a self-assembled condensate material, the raw materials for its preparation include: polyethylene glycol, silicotungstic acid and astaxanthin;
[0007] The self-assembled condensate material is a translucent dense condensate phase.
[0008] In combination with the first aspect, preferably, the astaxanthin is an ethanol solution of 0.25-0.5 mg / mL astaxanthin.
[0009] In combination with the first aspect, preferably, the astaxanthin is a 0.5 mg / mL astaxanthin ethanol solution.
[0010] In combination with the first aspect, preferably, the polyethylene glycol is a 0.4-0.8 g / mL polyethylene glycol aqueous solution.
[0011] In combination with the first aspect, preferably, the polyethylene glycol is a 0.6 g / mL polyethylene glycol aqueous solution.
[0012] In combination with the first aspect, preferably, the silicotungstic acid is a 0.6-1.0 g / mL silicotungstic acid aqueous solution.
[0013] In combination with the first aspect, preferably, the silicotungstic acid is a 0.86 g / mL silicotungstic acid aqueous solution.
[0014] The second aspect of the present application provides a method for preparing the self-assembled condensate material according to the first aspect, the method comprising:
[0015] The polyethylene glycol aqueous solution, the silicotungstic acid aqueous solution and the astaxanthin ethanol solution are mixed and reacted, and then completely phase separated after standing, and then separated and collected to obtain the self-assembled coacervate material.
[0016] In combination with the second aspect, preferably, the volume ratio of the polyethylene glycol aqueous solution to the silicotungstic acid aqueous solution is (1-2):(2-3).
[0017] The third aspect of the present application provides the use of the self-assembled condensate material prepared by the preparation method described in the second aspect in the preparation of tissue filling materials, embolic agents, and drug carriers.
[0018] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:
[0019] The self-assembled coacervate material provided in the present application is a translucent dense coacervate phase formed by polyethylene glycol, silicotungstic acid and astaxanthin. On the one hand, it can drive molecular self-assembly through hydrogen bonding, thereby improving the adhesion strength of the coacervate material and promoting its retention on the wound surface; on the other hand, the introduction of astaxanthin can not only reduce the particle size of the coacervate material and promote the release of active substances, but also change the electronic state of the coacervate material, while giving the coacervate material excellent injection performance; thirdly, it can make the self-assembled coacervate material have excellent antibacterial properties, antioxidant properties and anti-inflammatory properties at the same time, and it has low cost, can be mass-produced, and has good application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0021] Figure 1 This is a physical picture of the A1-self-assembled condensate material prepared in the embodiment of the present application before and after the mixing reaction;
[0022] Figure 2Transmission electron micrographs of the A1-self-assembled condensate material and the B1-condensate material prepared in the examples of the present application;
[0023] Figure 3 This is the infrared spectrum of the A1-self-assembled condensate material prepared in the examples of the present application;
[0024] Figure 4 This is the XPS graph of the A1-self-assembled condensate material prepared in the embodiment of the present application;
[0025] Figure 5 Atomic force microscope images of the A1-self-assembled condensate material and the B1-condensate material prepared in the examples of the present application;
[0026] Figure 6 Adhesion strength diagram of A1-self-assembled condensate material and B1-condensate material prepared in the examples of the present application;
[0027] Figure 7 The injection performance diagram of the A1-self-assembled condensate material and the B1-condensate material prepared in the examples of the present application;
[0028] Figure 8 The antibacterial effect diagram of the A1-self-assembled condensate material and the B1-condensate material prepared in the examples of the present application;
[0029] Fig. 9 A graph showing the ability of the A1-self-assembled condensate material and the B1-condensate material prepared in the examples of the present application to inhibit hydroxyl radicals;
[0030] Fig.10 This is a test chart of the anti-inflammatory properties of the A1-self-assembled condensate material and the B1-condensate material prepared in the examples of the present application. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.
[0032] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B may represent: A exists alone, B exists alone, and A and B exist at the same time. A and B may be singular or plural.
[0033] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0034] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0035] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0036] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.
[0037] In a first aspect, the present application provides a self-assembled condensate material, the raw materials for its preparation include: polyethylene glycol, silicotungstic acid and astaxanthin;
[0038] The self-assembled condensate material is a translucent dense condensate phase.
[0039] Among them, on the one hand, it can drive molecular self-assembly through hydrogen bonding, thereby improving the adhesion strength of the condensate material and promoting its retention on the wound surface; on the other hand, the introduction of astaxanthin can not only reduce the particle size of the condensate material and promote the release of active substances, but also change the electronic state of the condensate material, while giving the condensate material excellent injection performance; thirdly, it can make the self-assembled condensate material have excellent antibacterial properties, antioxidant properties and anti-inflammatory properties, and it has low cost, can be mass-produced, and has good application value.
[0040] In the embodiment of the present application, the astaxanthin is preferably an ethanol solution of 0.25-0.5 mg / mL astaxanthin, more preferably an ethanol solution of 0.5 mg / mL astaxanthin. Among them, by controlling the amount of astaxanthin added, not only can a uniform and stable condensate material structure be formed, but also the condensate material can be endowed with excellent antibacterial properties, antioxidant properties and anti-inflammatory properties, while reducing the particle size of the material, increasing the adhesion strength of the material, and improving the injection performance of the material, which has good application value.
[0041] In the embodiment of the present application, the polyethylene glycol is preferably a polyethylene glycol aqueous solution of 0.4-0.8 g / mL, more preferably a polyethylene glycol aqueous solution of 0.6 g / mL; the silicotungstic acid is preferably a silicotungstic acid aqueous solution of 0.6-1.0 g / mL, more preferably a silicotungstic acid aqueous solution of 0.86 g / mL. Among them, by controlling the addition amount of polyethylene glycol and silicotungstic acid, a physical cross-linked network of agglomerates constructed by hydrogen bond complexation can be formed, which has a certain fluidity, has excellent wetting performance at irregular wound surfaces, can completely fill defects, and is conducive to maintaining its integrity at the wound surface.
[0042] In a second aspect, the present application also provides a method for preparing the self-assembled condensate material according to the first aspect, the method comprising:
[0043] The polyethylene glycol aqueous solution, the silicotungstic acid aqueous solution and the astaxanthin ethanol solution are mixed and reacted, and then completely phase separated after standing, and then separated and collected to obtain the self-assembled coacervate material.
[0044] It should be noted that after the preparation method adopted in the present application reacts at room temperature and stands for 2 hours, the system is completely phase-separated, and a translucent dense condensed phase is formed at the bottom, which is a self-assembled condensate material. This process is more convenient for adjusting the mixing ratio of the materials, can form a uniform mixed phase, has a simple preparation process, low cost, and is easy to mass produce.
[0045] In the embodiment of the present application, the volume ratio of the polyethylene glycol aqueous solution to the silicotungstic acid aqueous solution is preferably (1-2): (2-3). Among them, by controlling the volume ratio of the polyethylene glycol aqueous solution to the silicotungstic acid aqueous solution, the yield of the aggregate material can be greatly improved.
[0046] The third aspect of the present application provides the use of the self-assembled coacervate material prepared by the preparation method of the second aspect in the preparation of tissue filling materials, embolic agents, and drug carriers. Among them, the self-assembled coacervate material prepared based on the above preparation has excellent self-assembly structure, adhesion strength, injection performance, antibacterial performance, antioxidant and anti-inflammatory properties, which can give it excellent product competitiveness.
[0047] The technical solution of the present application will be further described below in conjunction with specific embodiments.
[0048] Example 1
[0049] This embodiment provides a method for preparing an Al-self-assembled condensate material, which specifically includes:
[0050] A 0.5 mg / mL astaxanthin ethanol solution, a 0.6 g / mL polyethylene glycol aqueous solution and a 0.86 g / mL silicotungstic acid aqueous solution were mixed for reaction (the volume ratio of polyethylene glycol aqueous solution: silicotungstic acid aqueous solution was 2:3), and a high-viscosity substance was formed by vigorous stirring or violent shaking. After standing for 2 hours, the system was completely phase-separated, and the translucent dense condensed phase formed at the bottom was separated and collected to obtain the A1-self-assembled condensate material.
[0051] Example 2
[0052] This embodiment provides a method for preparing an A2-self-assembled condensate material, which specifically includes:
[0053] A 0.25 mg / mL astaxanthin ethanol solution, a 0.6 g / mL polyethylene glycol aqueous solution and a 0.86 g / mL silicotungstic acid aqueous solution were mixed for reaction (the volume ratio of polyethylene glycol aqueous solution: silicotungstic acid aqueous solution was 2:3), and a high-viscosity substance was formed by vigorous stirring or violent shaking. After standing for 2 hours, the system was completely phase-separated, and the translucent dense condensed phase formed at the bottom was separated and collected to obtain the A2-self-assembled condensate material.
[0054] Example 3
[0055] This embodiment provides a method for preparing an A3-self-assembled condensate material, which specifically includes:
[0056] A 0.4 mg / mL astaxanthin ethanol solution, a 0.6 g / mL polyethylene glycol aqueous solution and a 0.86 g / mL silicotungstic acid aqueous solution were mixed for reaction (the volume ratio of polyethylene glycol aqueous solution: silicotungstic acid aqueous solution was 2:3), and a high-viscosity substance was formed by vigorous stirring or violent shaking. After standing for 2 hours, the system was completely phase-separated, and the translucent dense condensed phase formed at the bottom was separated and collected to obtain the A3-self-assembled condensate material.
[0057] At the same time, in order to verify the comprehensive performance of the self-assembled condensate material prepared in the above examples, the present application provides the following comparative examples for detailed description.
[0058] Comparative Example 1
[0059] The component ratio, preparation operation and process parameters of the B1-agglomerate material prepared in the embodiment of the present application are basically the same as those in Example 1, except that in this embodiment, no astaxanthin is added to prepare the B1-agglomerate material.
[0060] Comparative Example 2
[0061] The composition ratio, preparation operation and process parameters of the B2-material prepared in the example of the present application are basically the same as those in Example 1, with the difference that the concentration of astaxanthin added in this example is 0.7 mg / mL, and after the reaction, a dense condensed phase structure cannot be formed, that is, when the concentration of astaxanthin is greater than 0.5 mg / mL, a self-assembled condensate material cannot be obtained, and therefore no further performance testing is performed.
[0062] Comparative Example 3
[0063] The composition ratio, preparation operation and process parameters of the B3-material prepared in the embodiment of the present application are basically the same as those in Example 1, except that the concentration of astaxanthin added in this embodiment is 0.2 mg / mL. After the reaction, that is, when the concentration of astaxanthin is less than 0.25 mg / mL, the B3-agglomerate material is prepared.
[0064] In order to verify the structural properties of the self-assembled condensate material prepared in the examples of the present application, the self-assembled condensate material prepared in the examples was characterized, and the results were as follows: Figures 1 to 5 As shown; among them, Figure 1 This is the actual picture of A1-self-assembled condensate material before and after the reaction; Figure 2 Transmission electron microscope images of A1-self-assembled condensate material and B1-condensate material; Figure 3 This is the infrared spectrum of A1-self-assembled condensate material; Figure 4 This is the XPS image of A1-self-assembled condensate material; Figure 5 Atomic force microscopy images of A1-self-assembled condensate material and B1-condensate material.
[0065] according to Figure 1 As known, these are the actual pictures before and after the mixing reaction for preparing A1-self-assembled coacervate material, a) before the mixing reaction of astaxanthin ethanol solution, polyethylene glycol aqueous solution and silicotungstic acid aqueous solution, the solution presents a turbid suspension structure, b) after the reaction, a uniform, stable, transparent and phase-separated structure of the reaction liquid is generated, and the translucent dense coacervate phase formed at the bottom is separated and collected to obtain the self-assembled coacervate material.
[0066] according to Figure 2 As known, the prepared A1-self-assembled coacervate material and B1-coacervate material were added to ethanol solution for dispersion, and dispersed evenly by ultrasound for 5 minutes. The material morphology was observed under a transmission electron microscope. a) is the B1-coacervate material, and b) is the transmission electron microscope image of the A1-self-assembled coacervate material. The self-assembled structure is shown by the transmission electron microscope image, and with the increase of astaxanthin concentration (0.25mg / mL-0.5mg / mL), the structure size decreases, indicating that the addition of astaxanthin can significantly reduce the structure size of the coacervate material.
[0067] according to Figure 3 As known, the prepared A1-self-assembled condensate material was freeze-dried, and the obtained different condensate compositions were characterized using the total reflection mode of Fourier transform infrared spectrometer. Figure 3 Infrared spectroscopy showed that the Keggin structure of silicotungstic acid (SiW) was well maintained, and the maximum displacement of COC stretching in the polyethylene glycol (PEG) group was 19 cm -1 , and 1093 cm before and after condensation -1 and 1074cm -1 , the driving force for the aggregation is the hydrogen bonding interaction between the oxygen atoms of SiW and the ether oxygen of polyethylene glycol.
[0068] according to Figure 4 As known, the prepared A1-self-assembled condensate material was freeze-dried in a freeze dryer, and its surface chemical composition was characterized by X-ray photoelectron spectroscopy (XPS). The A1-self-assembled condensate material group has different states of carbon at 286.28eV, i.e., C=O / C=C, and different states of oxygen at 532.68eV, i.e., C=O, which can indicate that the addition of astaxanthin in the system can change the electronic state of the condensate material.
[0069] according to Figure 5 As known, the morphology of the prepared A1-self-assembled condensate material and B1-condensate material was observed by atomic force microscopy. According to the figure, a) is the B1-condensate material, and b) is the A1-self-assembled condensate material, indicating that with the addition of astaxanthin, the self-assembly process of the condensate material.
[0070] In order to verify the performance of the self-assembled condensate material prepared in the examples of the present application, the self-assembled condensate material prepared in the examples was characterized, and the results were as follows: Figures 6 to 9 As shown; among them, Figure 6 Adhesion strength diagram of A1-self-assembled condensate material and B1-condensate material; Figure 7 The injection performance diagrams of A1-self-assembled condensate material and B1-condensate material; Figure 8 The antibacterial effect diagram of A1-self-assembled condensate material and B1-condensate material; Fig. 9 The hydroxyl radical inhibition ability diagram of A1-self-assembled condensate material and B1-condensate material; Fig.10 This is a test diagram of the anti-inflammatory properties of A1-self-assembled condensate material and B1-condensate material.
[0071] according to Figure 6As known, the adhesion properties of the prepared A1-self-assembled coacervate material and B1-coacervate material were tested using a texture analyzer, and the coacervate material was subjected to a tensile test on the texture analyzer. In the tensile test, the adhesion area was a circular pig skin with a radius of 0.75 cm. The test equipment was assembled, a sample volume of 10 μl was applied, and the test was performed at a test speed of 1 mm / s. Figure 6 As shown in the figure, the adhesion of different groups of coacervate materials can be seen from the figure that the adhesion performance is greatly improved after adding astaxanthin.
[0072] according to Figure 7 As known, the injection performance of the prepared A1-self-assembled coacervate material and B1-coacervate material was tested using a texture analyzer. During the downward pressure process, a 1mL syringe and an 18G injection head were selected and tested at a test speed of 0.5mm / s. This shows that the addition of astaxanthin can reduce the injection force of the coacervate material and expand the application range of the material.
[0073] according to Figure 8 As known, the prepared antibacterial properties against Staphylococcus aureus and Escherichia coli were tested, wherein 8a) is the colony picture after B1-coacervate material was in contact with Escherichia coli, 8b) is the colony picture after A1-self-assembled coacervate material was in contact with Escherichia coli, 8c) is the colony picture after B1-coacervate material was in contact with Staphylococcus aureus, and 8d) is the colony picture after A1-self-assembled coacervate material was in contact with Staphylococcus aureus. The specific operation is as follows: take out the streaked Staphylococcus aureus and Escherichia coli plates from the 4°C refrigerator and place them in the clean bench for operation. Use a sterilized inoculation loop to take single colonies and place them in 10mL of Luria-Bertani (LB) medium, and culture them overnight at 37°C and 150rpm. Take the bacterial solution after overnight and measure its OD with an enzyme marker. 630 , dilute the bacterial solution to 105CFU / mL for later use. Take 0.5g of the prepared coagulant material and add it to a 48-well plate, then drop 1mL of the diluted bacterial solution into it, and only put 1mL of the diluted bacterial solution in the control group, and put the above-mentioned well plate into a 37°C incubator for overnight incubation. After the incubation is completed, the plate is coated, and the agar plate is divided into three parts for parallel samples. 30μL of the incubated bacterial solution is dripped on each part, and then it is evenly coated in this area with a disposable coating rod. The coated agar plate is placed in a 37°C incubator for overnight incubation. After the incubation is completed, the agar plate is placed under a colony counter for photography. It can be clearly seen from the figure that the obtained coagulant material has a strong antibacterial effect, with an antibacterial activity of 98% against Escherichia coli and 99% against Staphylococcus aureus.
[0074] according to Fig. 9As known, the antioxidant properties of the prepared A1-self-assembled condensate material and B1-condensate material were tested. The antioxidant test was carried out by using a hydroxyl radical kit (Nanjing Jiancheng Bioengineering Institute). According to the instructions of the kit, the required reagents, including standard application solution, substrate application solution, color developer, etc., were prepared. According to the instructions, blank tubes, standard tubes, control tubes and assay tubes were set up, and appropriate reagents and samples were added. After the reaction was completed, the absorbance value of each tube at 550nm was measured. According to the measured data, the hydroxyl radical scavenging ability was calculated using the provided calculation formula as shown in Formula 1:
[0075] Hydroxyl free radical inhibition ability (U / mL) = (A 对照 -A 测定 ) / (A 标准 -A 空白 )×c 标准 ×1 / V 样 ×N;
[0076] Among them, C 标准 : Standard concentration, 8.824mmol / L; V 样 : sampling volume, 0.2mL; N: dilution multiple of sample before testing;
[0077] The hydroxyl radical scavenging ability of the coacervate material prepared in the example, and as the astaxanthin concentration increases, its hydroxyl radical scavenging ability becomes stronger. It can be seen from the figure that the prepared A1-self-assembled coacervate material has good antioxidant ability.
[0078] according to Fig.10 As known, the anti-inflammatory properties of the prepared A1-self-assembled coacervate material and B1-coacervate material were tested, a) B1-coacervate material, b) A1-self-assembled coacervate material. The cultured macrophages were seeded into a six-well plate, and after adding LPS solution, they were co-cultured with the extracts of A1-self-assembled coacervate material and B1-coacervate material, respectively, and then tested by flow cytometry. Fig.10 The results show that the prepared A1-self-assembled condensate material has good anti-inflammatory ability.
[0079] The performance of the self-assembled aggregate materials prepared in the examples and comparative examples of the present application was tested, and the results are shown in Table 1.
[0080] Table 1 Comprehensive properties of self-assembled condensate materials
[0081]
[0082] The adhesion, antioxidant and anti-inflammatory properties of the condensed materials prepared in Comparative Examples 1 and 3 of the present application are significantly lower than those of the condensed materials prepared in the examples. Therefore, the self-assembled condensed materials provided in the present application can drive molecular self-assembly through hydrogen bonding through the translucent dense condensed phase formed by polyethylene glycol, silicotungstic acid and astaxanthin, improve the adhesion strength of the condensed materials, and promote their retention on the wound surface; not only can the particle size of the condensed materials be reduced, the release of active substances can be promoted, but also the electronic state of the condensed materials can be changed, and at the same time, the materials are given excellent injection performance; the self-assembled condensed materials can have excellent antibacterial properties, antioxidant properties and anti-inflammatory properties at the same time, and large-scale production can be achieved, and they have good application value.
[0083] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.
[0084] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.
Claims
1. A self-assembled aggregate material, characterized in that: The raw materials for its preparation include: polyethylene glycol, silicotungstic acid and astaxanthin; The self-assembled condensate material is a translucent dense condensate phase.
2. The self-assembled aggregate material according to claim 1, characterized in that: The astaxanthin is an ethanol solution of astaxanthin at a concentration of 0.25-0.5 mg / mL.
3. The self-assembled aggregate material according to claim 1, characterized in that: The astaxanthin is a 0.5 mg / mL astaxanthin ethanol solution.
4. The self-assembled aggregate material according to claim 1, characterized in that: The polyethylene glycol is a 0.4-0.8 g / mL polyethylene glycol aqueous solution.
5. The self-assembled aggregate material according to claim 1, characterized in that: The polyethylene glycol is a 0.6 g / mL polyethylene glycol aqueous solution.
6. The self-assembled aggregate material according to claim 1, characterized in that: The silicotungstic acid is a 0.6-1.0 g / mL silicotungstic acid aqueous solution.
7. The self-assembled aggregate material according to claim 1, characterized in that: The silicotungstic acid is a 0.86 g / mL silicotungstic acid aqueous solution.
8. A method for preparing a self-assembled condensate material according to any one of claims 1 to 7, characterized in that: The method comprises: The polyethylene glycol aqueous solution, the silicotungstic acid aqueous solution and the astaxanthin ethanol solution are mixed and reacted, and then completely phase separated after standing, and then separated and collected to obtain the self-assembled coacervate material.
9. The self-assembled aggregate material according to claim 1, characterized in that: The volume ratio of the polyethylene glycol aqueous solution to the silicotungstic acid aqueous solution is (1-2):(2-3).
10. Use of the self-assembled condensate material prepared by the preparation method according to any one of claims 8 to 9 in the preparation of tissue filling materials, embolic agents and drug carriers.
